Waqf in Zaydī Yemen Legal Theory, Codification, and Local Practice - Hovden, Eirik (Brill, 2018)
Islamic foundations (waqf, pl. awqāf) have been an integral part of Yemeni society both for managing private wealth and as a legal frame for charity and public infrastructure. This book focuses on four socially grounded fields of legal knowledge: fiqh, codification, individual waqf cases, and everyday waqf-related knowledge. It combines textual analysis with ethnography and seeks to understand how Islamic law is approached, used, produced, and validated in selected topics of waqf law where there are tensions between ideals and pragmatic rules. The study analyses central Zaydī fiqh works such as the Sharḥ al-azhār cluster, imamic decrees, fatwās, and waqf documents, mostly from Zaydī, northern Yemen.